"Biting one's lip" and "distancing": exploring pre-service teachers' strategies in dysfunctional professional relationships. Issue 4 (8th August 2018) - O'Grady, Emmanuel; Guilfoyle, Liam; McGarr, Oliver
ABSTRACT: Pre-service teachers (PSTs) are often placed in a vulnerable position during their school placement. Recognising the presence of power dynamics between PSTs, university-based tutors, and cooperating teachers as well as exploring how PSTs navigate these power relations is the focus of this paper. Data from interviews with final-year PSTs were analysed using a directed content analysis exploring the issues of autonomy and agency evident within participants' descriptions of school placement. A finding of interest was the manner in which the PSTs cope with dysfunctional professional relationships. The over-riding approach appears to be compliance and silencing their professional voice. This was evident in the "biting one's lip" and "distancing" that occurred when PSTs experienced practices which were incongruent with the university expectations, or their own personal views, of teaching and learning. The implications for teacher education and tutors' facilitation of appropriate reflection are discussed.